A Novel Prognostic Indicator in Testicular Cancer Patients: Mean Platelet Volume - Sacit Nuri GÖRGEL; Yiğit AKIN; Esra Meltem KOÇ; Osman KÖSE; Serkan ÖZCAN; Yüksel YILMAZ (Forbes Tıp Dergisi, 2022)
Objective: Testicular cancer (TCa) is still the most frequent solid organ cancer in men aged 15-35 years. Mean platelet volume (MPV) alteration is used as an indicator in some cancer. We evaluated MPV levels and their significance as one of the prognostic factors in TCa. Methods: Between January 2006 and October 2019, all TCa data of our clinic were researched. Total of 133 patients diagnosed with TCa enrolled. Age, tumor size, blood tests, clinicopathological data including lymphovascular invasion, pathological stage, invasion of epididymis, spermatic cord, surgical margin, retroperitoneal lymph node involvement in radiological examinations, and metastasis were recorded. The potential prognostic value of MPV was evaluated using receiver operating characteristics (ROC) curves. Prognostic factors were analyzed. Significant p was p<0.05. Results: The mean age was 39.22+-10.25 years old and optimal cut-off value of MPV for disease-specific survival (DSS) was 7.9 fL in ROC curve analysis. Progression for DSS was worse for decreased MPV in Kaplan-Meier analyses (p<0.001). Univariate analyses showed that preoperative human chorionic gonadotropin and MPV were statistically significant prognostic factors (respectively; p=0.002, p<0.001). MPV was the only factor that was determined as an independent prognostic factor in multivariate cox regression model (p<0.001). The optimal cut-off value of MPV for DSS was 8.37 fL in ROC analysis. Decreased MPV levels also presented poor progression for overall survival (OAS) (p<0.001). Conclusion: Decreased MPV levels can be defined as one of the risk factors in TCa patients for DSS. There is also a risk of poor OAS in TCa patients with decreased MPV.